A risk stratification model for toxicities in phase 1 immunotherapy trials. (November 2022) - Hernando-Calvo, Alberto; Salawu, Abdulazeez; Chen, Rachel Y.; Araujo, Daniel V.; Oliva, Marc; Liu, Zhihui Amy; Siu, Lillian L.
Abstract: Introduction: Despite the increased number of novel immunotherapy (IO) agents under current development, their toxicity profile remains to be fully elucidated. Methods: An IO risk stratification model was developed based on 5 different variables: treatment-related deaths; rate of grade ≥3 treatment-related adverse events or treatment-emergent adverse events; grade ≥2 encephalopathy or central nervous system toxicity; grade ≥2 cytokine release syndrome; and the number and type of dose-limiting toxicity. Phase 1 IO trials published from January 2014 to December 2020 were reviewed and categorised based on our risk stratification model into three categories: low-, intermediate- and high-risk. Clinical trial variables were associated with the high-risk category. To review the quality of reporting across phase 1 IO trials, a subset of studies was further examined by the use of the ASCO/SITC Trial Reporting in Immuno-Oncology (TRIO) standards. Results: Different IO compounds demonstrated diverse risk profiles. In multivariable analysis, combination versus IO single agent treatment, and testing IO agents different from anti-programmed death-1/programmed death ligand-1 (anti-PD1/L1), anti-cytotoxic t-lymphocyte antigen-4 (anti-CTLA4) antibodies and anti-cancer vaccines were associated with a higher toxicity risk. None of the studies examined in our dataset reported all the items included in the TRIO standards. Conclusions: Our results have important implications for future clinical trial design. Additionally, standards for reporting are urgently needed. Highlights: The toxicity of novel immunotherapy (IO) agents remains to be fully elucidated. A risk stratification model for phase 1 IO clinical trials was developed. Published phase 1 trials were classified into low-, intermediate- or high-risk. IO regimen and IO class were associated with different risks of toxicity.